Program Pembelajaran Individual untuk Meningkatkan Konsentrasi Bagi Anak Dengan Attention Deficit Hyperactyvity Disorder (Adhd) di SD GMIM VI Tomohon - Moningka, Angel Dini; Dapa, Aldjon Nixon; Marentek, L.K.M.; Siwi, Femmy D. (Jurnal Ilmiah Wahana Pendidikan, 2024)
Learning in inclusive education schools, which have students with very varied abilities, is different from regular schools where students generally have uniform levels of ability. Most teachers in inclusive schools are not prepared to teach children with disabilities or special needs, so they often have difficulty in developing appropriate individual learning programs. In this study, the method used is the ADDIE R&D development model, which includes five stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation The purpose of this study is to develop one product, namely PPI (Individual Learning Program). The Individual Learning Program (PPI) is very influential and proven to be effective for learning in inclusive schools because students with special needs can follow the existing learning, the learning outcomes obtained have also changed since implementing the Individual Learning Program (PPI) in regular schools. Based on data analysis from the results of the study and discussion, it can be concluded that the PPI (Individual Learning Program) in regular schools has a very significant influence on the student learning process by looking at the evaluation and instrument of the PPI (Individual Learning Program) that is carried out